Note to Kathleen O'Brennan, Honorary Secretary, from Talbot Press on behalf of Miss Mary Flynn, about books to be exhibited by the Dublin P.E.N. Club at an upcoming Book Fair, - Talbot Press (Dublin, Ireland) (1945)
Kathleen O'Brennan requested books for a Book Fair in the Mansion House in September 1945 being held in connection with the Thomas Davis Centenary. The writer refers to 'Cornelius Rabbit of Tang'.